2022
DOI: 10.1215/00703370-9709538
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Age Patterns of Under-5 Mortality: Results From a Log-Quadratic Model Applied to High-Quality Vital Registration Data

Abstract: Information about how the risk of death varies with age within the 0–5 age range represents critical evidence for guiding health policy. This study proposes a new model for summarizing regularities about how under-5 mortality is distributed by detailed age. The model is based on a newly compiled database that contains under-5 mortality information by detailed age in countries with high-quality vital registration systems, covering a wide array of mortality levels and patterns. It uses a log-quadratic approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Below the threshold, all infants are equally susceptible to infection and have a constant risk of hospitalized dengue disease upon infection, independent of antibody concentrations (non-ADE scenario). For both of these scenarios, we also consider model versions where infant vulnerability to hospitalized disease given a DENV infection declines exponentially from birth as a function of infant age, consistent with underlying frailty decreasing over the first year of life ( 16 , 17 ). We find that the ADE scenario is able to reconstruct the observed age distribution of hospitalized infant dengue cases, both with and without an age-specific disease vulnerability effect ( SI Appendix , Table S3 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Below the threshold, all infants are equally susceptible to infection and have a constant risk of hospitalized dengue disease upon infection, independent of antibody concentrations (non-ADE scenario). For both of these scenarios, we also consider model versions where infant vulnerability to hospitalized disease given a DENV infection declines exponentially from birth as a function of infant age, consistent with underlying frailty decreasing over the first year of life ( 16 , 17 ). We find that the ADE scenario is able to reconstruct the observed age distribution of hospitalized infant dengue cases, both with and without an age-specific disease vulnerability effect ( SI Appendix , Table S3 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Predictions can be obtained from any single mortality rate within the age range 0 years to 5 years ( appendix p 2). 4 …”
Section: Methodsmentioning
confidence: 99%
“…3 Greater precision in empirical estimates of age-specific mortality is also necessary for modelling mortality in settings in which empirical data are not available. 4,5 Case studies focusing on rural zones of The Gambia and Senegal between 1961 and 1983 identified an unusual age pattern of under-5 mortality. 3,[6][7][8] A 1985 study 8 summarised these findings and showed that, in these populations, mortality was 2-to-3 times higher between the ages of 1 year and 5 years than would be expected on the basis of Brass's African Standard (an existing model for mortality in Africa).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations